1994
DOI: 10.1055/s-0038-1642375
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Measurement of D-Dimer as Diagnostic Aid in Suspected Venous Thromboembolism: An Overview

Abstract: SummaryThis paper reviews the published experience with plasma measurement of D-dimer (DD), a specific degradation product of crosslinked fibrin, in the diagnostic approach of venous thromboembolism (VTE). Pooling 11 studies (with weighting of the figures according to sample size) with a total of 1337 patients clinically suspected of deep venous thrombosis (DVT) (prevalence of DVT 35%) disclosed an average weighted sensitivity of 96.8% (95% CI: 95.2–98.4) and specificity of 35.2% (95% Cl: 32.0–38.4) for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
191
1
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(207 citation statements)
references
References 34 publications
(28 reference statements)
8
191
1
7
Order By: Relevance
“…Results of thrombotic marker assays in the patients showed that D. Dimer levels 19 were increased sevenfold as compared with the controls, whereas the levels of TAT and F 1+2 were normal in controls and in patients. Elevation of D. Dimer levels denotes activation of ®brin formation inside and even outside the vascular system and therefore indicates that clinical or subclinical thrombosis has occurred despite the administration of prophylactic anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Results of thrombotic marker assays in the patients showed that D. Dimer levels 19 were increased sevenfold as compared with the controls, whereas the levels of TAT and F 1+2 were normal in controls and in patients. Elevation of D. Dimer levels denotes activation of ®brin formation inside and even outside the vascular system and therefore indicates that clinical or subclinical thrombosis has occurred despite the administration of prophylactic anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We believe the diagnosis of UAP at admission to the ED should be based on clinical factors such as history, physical examination, and electrocardiography, and not on blood markers. Moreover, the generally low specificity of the available D-dimer assays (ELISA, latex agglutination assay, turbidometric immunoassays) and their wide variations in sensitivity [16][17][18] preclude their use as a diagnostic tool [16,[19][20][21][22]. Because of the low interassay correlation [21,22] and the lack of a D-dimer reference standard, we used the ELISA, which is currently considered the gold-standard methodology.…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be a valuable additional test to exclude thrombo in the first period of suspected DVT as v/ell as in recur rent signs of DVT. Further research, such as management studies in patients clinically sus pected of DVT, has to be performed [127]. Also, more rapid D D tests (more sensitive latex assays or more rapid E LISA 's) have to be developed [128].…”
Section: Npv (%)mentioning
confidence: 99%